The sea of trolls - Farmer, Nancy, 1941- (Simon Pulse, 2004)
After Jack become apprenticed to a Druid bard, he and his little sister Lucy are captured by Viking Berserkers and taken to the home of King Ivar the Boneless and his half-troll queen, leading Jack to undertake a vital quest to Jotunheim, home of the trolls.